Acid‐ and Base‐Stable Cs2Pt(Cl, Br)6 Vacancy‐Ordered Double Perovskites and Their Core–Shell Heterostructures for Solar Water Oxidation. Issue 7 (5th April 2022) - Hamdan, Muhammed; Manoj, Manasa; Halpati, Jigar Shaileshkumar; Chandiran, Aravind Kumar
Abstract : The stability of the absorber materials in an aqueous medium is the key to developing successful photoelectrochemical (PEC) solar fuel devices. The halide perovskite materials provide an opportunity to tune desired optoelectronic properties and show very high photovoltaic power conversion efficiency. However, their stability is poor as they decompose instantly in an aqueous electrolyte medium. Here the most stable vacancy ordered double perovskites Cs2 PtCl6 and Cs2 PtBr6, which remain intact in a wide range of pH values between 1 and 13 is reported. These materials also possess excellent absorption properties covering a significant portion of the visible spectrum. Like conventional ABX3 materials, these ultrastable materials offer tunability in optical properties via mixed halide sites. Through anion exchange, the conversion of Cs2 PtCl6 to Cs2 PtBr6 through core–shell conversion mechanism is shown. The latter led to the formation of type‐II heterostructures. The electrochemical properties of these materials are investigated in detail and their ability to carry out solar water oxidation on an unprotected photoanode, with photocurrent density of >0.2 mA cm −2 at 1.23 V (vs. RHE) is demonstrated. Abstract : The most stable vacancy‐ordered halide double perovskite material based on Cs2 Pt(Cl, Br)6, which remains intact in harsh pH conditions and shows panchromatic visible light absorption is reported. Through an anion‐exchange process, core–shell heterostructures of Cs2 PtBr6 /Cs2 PtCl6 with type‐II band alignment are obtained. These structures were employed as photoanodes without any surface protection for solar water oxidation.